Analysis of High-Tension Cable Median Barrier Crashes and Associated Severities - Ash, John (My University, 2014)
Often severe, cross median crashes (CMCs) are crashes in which a vehicle enters the roadway median, fully traverses it, and enters the opposing traveled way. Their severe nature stems from the fact that they often result in fatal head-on collisions. In an effort to prevent CMCs, many transportation agencies have installed high-tension cable median barriers along their highways. At this point in time, the literature has shown that cable median barriers do in fact help prevent CMCs, although often at the expense of an increase in the frequency of lower-severity crashes. Currently, however, little is known about factors influencing cable median barrier crash severity and crash outcome. This thesis investigates these issues through a variety of statistical analyses. Logistic regression analyses of barrier containment showed factors such as AADT, number of cables in the barrier cross-section, and occurrence of another crash prior to and/or after the barrier hit to significantly affect the likelihood of stopping an errant vehicle upon impact. Analysis of barrier breach crashes showed that in general, they result in higher severity than non-breach crashes and that the majority of vehicles breaching cable barriers were not heavy vehicles. Regression analyses of crash severity associated with cable median barrier crashes showed that pavement condition at the time of the crash can influence crash severity. Further, when examining models for all injury crashes regardless of severity, crash outcome and occurrence of another collision prior to the barrier hit were shown to influence the odds of a barrier crash resulting in injury.